Analisis Indikasi Kegagalan Transformator dengan Metode Dissolved Gas Analysis - Faishal AR, Muhammad; Karnoto, Karnoto; Sukmadi, Tejo (Departemen Teknik Elektro, Universitas Diponegoro, 2011)
A common problem in power transformers is the emergence of operational failures, both the failure of both thermal and electrical failures. Failure of the thermal and electrical failures generally produce harmful gases commonly known as the fault gas. Most power transformers typically use oil as an insulator that functions in addition to cooling also to dissolve the harmful gases in order not to circulate freely. The type and amount of dissolved gas concentrations in oil may provide information to the indication of failures in the transformer. Methods for identifying and analyzing the gases dissolved in oil is called as a method of DGA (Dissolved Gas Analysis). The final project is about the analysis of DGA test to identify indications of failures in the transformer. Analytical methods are used 4 methods that is TDCG (Total Dissolved Combustible Gas), Gas Key, Roger Ratio and Duval Triangle. IEEE Standards std.C57 - 104.1991 and IEC 60 599 is used as a benchmark analysis of test results of DGA. Analysis of DGA results test that have been made ​​to the IBT transformer 1 Phase R Ungaran Substation in 2005 and 2006, with TDCG method shows the transformer in condition 2, the key gas method shows have been an indication of thermal failure involving insulator paper as indicated by the concentration of CO gas whose value is 53% of the value of the total fault gas. Analysis by Roger's method and the Duval method indicated that there has been a thermal failure with a temperature between 1500C - 3000C and 3000C - 7000C. From the analysis of DGA results test in 2007 to 2011 shows the transformer in normal circumstances this is indicated by the value TDCG under 720 ppm. Keyword : DGA, oil transformer, DGA Analysis Method, Thermal Failure.